Risk factors in Implant Placement: A Retrospective Analysis (Indian Journal of Forensic Medicine & Toxicology, 2020)
Purpose: The aim of this retrospective study was to determine the prevalence of implant failure and its associated risk factors using a single implant system in our clinical setting Method: Patients who received implant treatment with a single implant system (MIS, Confident India) at Manipal College of Dental Sciences, Mangalore from 2010 to 2016 were enrolled. The following data were collected for analysis: patient details, field of expertise to which the surgeon belonged ,diameter and length of the implant, The outcomes assessed were early or delayed failure on the basis of operator , implant, anatomy and patient related factors . Results: This study analyzed 363 implants in 327 patients, who comprised 136 females and 191 males and were followed up until failure was reported after implant placement. 22 implants failed prior to final prosthesis delivery (early implant failure), and 5 implants were lost after prosthesis delivery. Out of 363 implants 206 (57%) implants were placed by the Department of Prosthodontics, 77(21%) by the Department of Periodontics and 69 (19%) by the Department of Oral surgery and remaining were placed by a single Endodontist (3%) specialized in Implantology.. (9/206=4%) failures were reported from Prosthodontics and 18 (18/69=26%) failures from Oral Surgery No failures were reported from Periodontics and Endodontics. Conclusions: Prospective studies are warranted to further elucidate the factors contributing to implant failure. In the meantime, surgeons should receive appropriate training and carefully select the bone bed in order to minimize the risk of implant failure.